A Translation Study of Informal Texts: "Tentang" Menu of Melung Village Website - Rizki Ratna Wulandari (Jurnal Vokasia, 2023)
This final project report is entitled ‘Translating “Tentang” Menu of Melung Village Website.’ This text was chosen to translate because it is informative and useful for readers, especially for foreigners who need information about the village using English language. This text explains the history, region, and institutions of Melung Village. The purposes of this internship are to translate the text and apply the knowledge of translation acquired during the course of study. The translation process was carried out from May to June 2023. There were three stages in translating these texts: analysis stage, transfer stage, and restructuring stage. In the first stage, the translator reads the entire transcript and capture the message in “Tentang” menu text. The transfer stage is carried out on the brain to transfer text from source language text to target language text. In the third stage, the text that has been processed in the first stage and second stage is rewritten until it became acceptable in the “Tentang” menu text. During the translation process of the “Tentang” menu text of the Melung Village website, the writer encountered several obstacles. The obstacles were finding the right diction in the target language to convey messages from the source language, searching and finding the equivalent word in the target language, and applying and editing the translation result into the website. The solutions to overcome the obstacles were searching information about the text in the source language, giving the description for the word was translated, and collaborating with the website management to edit and apply result of the translation on the website.